Ethnomathematics of Geometric Transformation in Knitting Mosaic Patterns with Terrazzo Motifs - Laili, Erviana Nur; Sulisawati, Dwi Noviani; Hidayatin, Nur (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Knitting activities not only involve elements of manual skills and art but also contain patterns closely related to mathematical concepts, particularly geometric transformations such as reflection, rotation, translation, and dilation. Therefore, this study intends to explain how the activity of knitting visual-based motifs can help understand the concept of geometric transformation. The study used a qualitative descriptive approach. Two knowledgeable lecturers verified the instrument the researchers developed through interview instructions and observations. The study's results reveal that reflection is the most commonly utilized transformation in the knitting process. This reflection appears in the form of symmetrical patterns, both with respect to the vertical, horizontal, and diagonal axes. In addition to reflection, the resulting patterns also show rotation with a specific center point, shifts (translations) in the repeating motifs, and changes in size (dilation) in several parts of the design. Visual strategies used in designing motifs include dividing the plane into certain parts to arrange the pattern in a balanced manner, determining a reference point as the center of rotation or enlargement, and using a grid-like arrangement to maintain the regularity of the shape. Based on these findings, it can be concluded that knitting motifs is an activity that emphasizes aesthetic aspects and provides an in-depth learning experience regarding the concept of geometric transformation. We can use this activity as a fun, alternative, and meaningful medium to understand geometry in a real and contextual way.